Relationship between Malay language writing skills and learning motivation among non-native speakers - Said, Rozita @ Radhiah; Nahar, Nora'azian; Mohd Kiram, Norazlina (Human Resource Management Academic Research Society, 2019)
The study was carried out to determine the relationship between Malay language (BM) writing skills and learning motivation among non-native speakers. A total of 414 research participants from 5 Chinese National-type primary schools (SJKC) and Tamil National-type primary schools (SJKT) in the district of Kuantan were selected for the study. Two instruments were developed which were a questionnaire to gauge learner motivation and a writing skill proficiency test for BM at primary school level (UPBM_SR). The study adopted a cross-sectional research design. Data was analysed using IBMSPSS version 23. Results from the writing test show that a majority of respondents achieved Level 1 (Very Minimal) at 25.1% (104 respondents), followed by Level 3 (Limited) at 20.3% (84 respondents), Level 2 (Minimal) at 19.8% (82 respondents), Level 4 (Fairly Skilful) at 14.5% (60 respondents), Level 5 (Almost Skilful) at 10.1% (42 respondents), Level 6 (Skilful) at 7.2% (30 respondents), and Level 7 (Skilful) at 2.9% (12 respondents). No respondents achieved Level 8 (Highly Skilful). The mean score for instrumental learning motivation was significant with r (412) = 0.22, p<.001 and the mean score for integrative learning motivation was also significant with r (412) = 0.18, p<.001. Based on Cohen’s (1998) interpretation, the relationship shown is small. Results of the linear regression (?=.20, p<.01) show that writing ability is not the main factor affecting the overall score of UPBM_SR. It is hoped that the findings of the study could enhance the knowledge of BM teachers in National-type schools across Malaysia. It is also hoped that the UPBM_SR instrument could be used to develop the BM proficiency of non-native speakers in primary schools in preparation for writing tests at higher levels of schooling.